Pengaruh dan Dampak Penerapan Strategi Penyelesaian Kredit Macet Terhadap Kinerja Keuangan Pada PT Tri Sapta Jaya Cabang Sibolga - Elsabeth Sigalingging; Yacub Hutabarat; Zafril Abdi Nasution (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This study aims to determine whether or not there is influence and impact of implementing bad loans on the company's financial performance at PT. Tri Sapta Jaya Sibolga Branch. Tri Sapta Jaya Sibolga Branch. This type of research used is descriptive quantitative. In this study the population is financial data and is used as a sample of financial reports and bad loans and the data source used is the type of data that is documentation and the data source used is secondary data. To analyze the data using descriptive analysis and quantitative analysis. Based on the results of the study, the relationship between the influence and the impact of the bad debt settlement strategy on financial performance was obtained based on the ratio (NPL) of Net performing loans and the ratio (ROE) of Return on Equity and inputted with SPSS results version 25. Final Results of Net Performing Loan (NPL) Research as much as 21.17%, Return On Equity (ROE), regression test results of 1.238, determination coefficient test 3.2%, the value of t table or 7.664 > 6.313 because the calculated t value is greater than t table then the alternative hypothesis (Ha ) is accepted, or the significance obtained is below the α level of 5%.